Multiorbital effects on CO ionization by intense short laser pulses. (25th August 2021) - Stroe, Marius Cristian; Fifirig, Magda
Abstract: Within time-dependent Hartree–Fock theory, we study the CO ionization for six different photon wavelengths running from 200 to 700 nm. The parallel and perpendicular alignments of the CO molecular axis with the polarization direction of the laser electric field are considered for two different laser intensities, namely 1.0 × 10 14 and 1.0 × 10 15 W cm −2 . At the laser intensity 1.0 × 10 14 W cm −2, the ionization picture is characterized by the dominance of the highest occupied molecular orbital, while at laser intensity 1.0 × 10 15 W cm −2 the inner valence molecular orbitals significantly contribute to the CO ionization. The present computations also reveal that orbital switching effects due to peak intensity variation may occur at some shorter wavelengths.